Integration of AI and OR Techniques in Constraint Programming for Combinatorial Optimization Problems Second International Conference, CPAIOR 2005, Prague, Czech Republic, May 31 -- June 1, 2005 - Barták, Roman; Milano, Michela (Theoretical Computer Science and General Issues, 2005)
The 2nd International Conference on Integration of AI and OR Techniques in Constraint Programming for Combinatorial Optimization Problems (CPAIOR2005)washeldinPrague,CzechRepublic,duringMay31-June1,2005. The conference is intended primarily as a forum to focus on the integration and hybridization of the approaches of constraint programming (CP), arti?cial intelligence (AI), and operations research (OR) technologies for solving large-scale and complex real-life optimization problems. Therefore, CPAIOR is never far from industrial applications. The high number of submissions received this year, almost 100 papers, in witness to the interest of the research community in this conference. From these submissions, we chose 26 to be published in full in the proceedings. This volume includes summaries of the invited talks of CPAIOR: one from industry, one from the embedded system research community, and one from the operations research community. The invited speakers were: Filippo Focacci from ILOGS.A.,France,oneoftheleadingcompaniesinthe?eld;PaulPop,professor in the Embedded Systems Lab in the Computer and Information Science - partment, Link¨ oping University; and Paul Williams, full professor of Operations Research at the London School of Economics. The day before CPAIOR, a Master Class was organized by Gilles Pesant, where leading researchers gave introductory and overview talks in the area of metaheuristics and constraint programming. The Master Class was intended for PhD students, researchers, and practitioners. We are very grateful to Gilles who brought this excellent program together. For conference publicity we warmly thank Willem Jan van Hoeve and Petr Vil´ ?m who did a great job with the high number of submissions received.